DIPG-12. PALLIATIVE TREATMENT FOR DIPG (DIFFUSE INTRINSIC PONTINE GLIOMA) AT KOBE CHILDREN'S HOSPITAL IN JAPAN. Issue 2 (22nd June 2018) - Kawamura, Atsufumi; Koyama, Junji; Akutsu, Nobuyuki; Azumi, Mai
Abstract: INTRODUCTION: Brain stem glioma is common pediatric brain tumor that accounts for 8~20% of them and diffuse intrinsic pontine glioma (DIPG) is the majority. The consensus treatment is radiotherapy but prognosis is very poor, thus most of the cases indicate tumor death and the average survival period is about a year. In most cases, neurosurgeon would be the first specialist doctor whom the family consult with and give the great influence to them. Therefore, it is necessary for us to lead the treatment and also palliative treatment in brain tumor care team at our institute. This report reflects our experience of palliative treatment for 19 DIPG cases in 265 central nervous system tumor from 2010 to 2017. CASES: All cases underwent irradiation with Temozoromide (TMZ) and one case has received re-radiation when symptoms and signs got worse after the first radiotherapy. Ventriculo-peritoneal shunt was placed in 5cases which indicated hydrocephalus caused by growth of tumor. RESULTS: The average survival period was 11.7 months and the last place for 6 cases were home, 10 cases were hospital and one was the hospice for childhood terminal disease. As for the administration period, under 1 day was 2 cases, under 5 days was 5, under one month was one and over a month was 2. CONCLUSION: To keep QOL for DIPG children, it is necessary to make the decision at appropriate time to be able to select the advanced treatments.